Decreased body mass index is associated with impaired survival in lung cancer patients with brain metastases: A retrospective analysis of 624 patients. (10th May 2017) - Masel, E.K.; Berghoff, A.S.; Füreder, L.M.; Heicappell, P.; Schlieter, F.; Widhalm, G.; Gatterbauer, B.; Dieckmann, U.; Birner, P.; Bartsch, R.; Schur, S.; Watzke, H.H.; et al.
Abstract : Body mass index (BMI) is a prognostic factor in several cancer types. We investigated the prognostic role of BMI in a large patient cohort with newly diagnosed lung cancer brain metastases (BM) between 1990 and 2013. BMI at diagnosis of BM and graded prognostic assessment (GPA) were calculated. Definitions were underweight (BMI <18.50), weight within normal range (BMI 18.50–24.99) and overweight (BMI ≥ 25.00). A total of 624 patients (men 401/624 [64.3%]; women 223/624 [35.7%]; median age of 61 [range 33–88]) were analysed. Histology was non‐small cell lung cancer in 417/622 (66.8%), small cell lung cancer (SCLC) in 205/624 (32.9%) and not otherwise specified in 2/624 (0.3%) patients. About 313/624 (50.2%) had normal BMI, 272/624 (43.5%) were overweight and 39/624 (6.3%) were underweight. Underweight patients had shorter median overall survival (3 months) compared to patients with normal BMI (7 months) and overweight (8 months; p  <   .001; log rank test). At multivariate analysis, higher GPA class (HR 1.430; 95% cumulative incidence, CI 1.279–1.598; p  <   .001; Cox regression model), SCLC histology (HR 1.310; 95% CI 1.101–1.558) and presence of underweight (HR 1.845; 95% CI 1.317–2.585; p  = .014; Cox regression model) were independent prognostic factors. Underweight at diagnosis of BM in lung cancer is associated with an unfavourable prognosis.